The dose of remimazolam combined with sufentanil for the induction of general anesthesia in obese patients undergoing bariatric surgery: an up-and-down sequential allocation trial - Chen, Minghui; Wang, Huiying; Sun, Jiajun; Zhang, Tao; Niu, Xiaoyin; Zhang, Tingting; Liu, Jian; Zhao, Xuan (Frontiers in Pharmacology, 2024)
Background and Purpose: Remimazolam is a newly developed benzodiazepine drug with watersoluble, esterase degradation and ultra-short acting properties. The dose for general anesthesia induction in obese patients was not known. This study aimed to determine the optimal dose of remimazolam in combination with sufentanil for the induction of general anesthesia in obese patients.It was a prospective observational study. We recruited 46 patients scheduled for bariatric surgery from October 2022 to December 2023. One patient refused to give informed consent and six patients were receiving psychotropic medication. Thirty-nine patients were enrolled. The modified observer's assessment of Alertness/Sedation scale (MOAA/S) was used to assess patients' response. The dose of sufentanil was 0.5 ug/kg (lean body weight, LBW). Initial dose of remimazolam was 0.3mg/kg (LBW). The dose of remimazolam was modified using the up-and-down allocation technique. Successful sedation (negative group) was characterized by achieving a MOAA/S score ≤1 within 3 minutes of commencing remimazolam infusion. If negative, the next patient received a lowlevel dose at a ratio of 0.9. Failed sedation (positive group) was defined as the MOAA/S score of ˃1 within 3 minutes of commencing remimazolam infusion. The patients in positive group received propofol 0.5mg/kg as a remedical measure and the next dose was increased to the higher level. The primary outcome was to determine the half-effective dose (ED50) and 95% effective dose (ED95) of remimazolam in combination with sufentanil 0.5ug/kg for induction in obese patients. The secondary outcome was to determine the occurrence of adverse effects such as hypotension, hypertension, intraoperative awareness.The ED50 and ED95 of remimazolam (LBW) combined with sufentanil 0.5 ug/kg (LBW) were 0.115 mg/kg (95% CI 0.072-0.137) and 0.179 mg/kg (95% CI 0.150-0.434) respectively and the time of loss of consciousness in negative group was 120.13±25.03 s. The cardiovascular system was stable during the induction period. The incidence of PONV was 38.5% in 39 patients. Respiratory depression, allergic reaction, intraoperative awareness and delayed emergence was not observed in any patient.Remimazolam combined with sufentanil 0.5ug/kg (LBW) can be effectively used for general anesthesia induction in obese patients. The ED50 and ED95 of remimazolam (LBW) were 0.115mg/kg and 0.179mg/kg respectively.